Marketing strategies in small animal clinical practice - Soares, Jose Antonio; Baptista Galvao, Andre Luiz [UNESP]; Shigaki de Matos, Lucas Vinicius [UNESP]; Pierucci, Julia Cestari [UNESP]; Saraiva Bresciani, Katia Denise [UNESP]; Pizzinatto, Nadia Kassouf (Emerald Group Publishing Ltd, 2017)
Purpose - Marketing strategies can be used to leverage business in the service sector, specifically in veterinary medicine; among other benefits, it can make a difference in satisfaction and consequent customer loyalty. Marketing should be used with ethics and professionalism due is one administration area that contributes to effective management in the continuous pursuit of quality in the provision of services and demonstrate that veterinary clinics have much to gain if managed with support of marketing strategies. This paper aims to analyze the applicability of marketing strategies in the management of small animal clinics, such as guidelines to the entrepreneurs of this services sector. Design/methodology/approach - Marketing literature is plentiful in proposing alternative strategies, whether focused on the achievement and loyalty of customers, whether to raise the competitiveness of an organization or simply to its survival in the market. In this study, some marketing strategies were selected, on secondary data research, in theoretical framework, to investigate their application in the practice of veterinary medicine. This study emphasizes promotional strategy toward communication with the market and construction of organizational image, using public relations as marketing strategy. Findings - The use of marketing strategies is recommended in the management of small animal clinical practice, especially with respect to the high customer satisfaction by streamlining the procedures and optimizing veterinary services provision. Originality/value - This study is different because it proposes an integrated system of management techniques in veterinary organizations, which will lead to better efficiency of attendance, adding value to the service provided and generating greater profitability for the organization, which positively reflects on the economic point of view and for the image of the company and its professionals, providing a better quality of life for both clients and their pets.
Keywords: Entrepreneurship; Marketing in veterinary medicine; Pet market; Veterinary clinic; Veterinary market